Effectiveness of Sentence Scramble Games to Improve Syntactic Abilities for a Student with Hearing Impairment - Riza Asri Yeta; Mega Iswari (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2019)
This article reviews the effectiveness of sentence scramble games to improve syntactic abilities of a student with hearing impairment who experienced difficulties while learning syntactic abilities even though the topic had been explained using flashcards. This research is an experimental study in the form of single subject research (SSR) with multiple baselines cross conditions design. The subject of the research is a student with hearing impairment. Data collection was performed through a written test and the data were in the form of student worksheets. The data were analyzed using a visual data analysis technique. Based on the results of the analysis of the intra-conditions and inter-condition of the classroom, computer room, and the boarding house, it was found that the syntactic abilities of the student with hearing impairment improved after an intervention using sentence scramble games was performed. The sentence scramble games have proven effective in improving the syntactic abilities of a student with hearing impairment.